The Development of Muslim Personality in the Light of the Surah al-Kahf - Lukmanul Hakim; Maher bin Ghazali; Basel Munir Hamdeh; Masyhuri Putra; Fatmah Taufiq Hidayat (Qur'an and Hadith Academic Society, 2023)
The muslim personality is characterized by awareness, thought, and a clear vision of the reality of the world, and this personality embodies positive constructive elements to be recruited to face all kinds of contemporary challenges, seeing the world in the light of Qur'anic guidance, steadfastness on divine principles and values, and contributing to changing society and rebuilding the earth, and this article deals with Aspects that contribute to making a global personality based on correct faith and broad-mindedness, including the doctrinal, scientific, practical and intellectual side through Surah al-Kahf. In order to achieve this, the inductive approach was used by following the sayings and ideas of scholars in ancient and modern interpretations. The analytical approach is also used in order to study, compare and classify sayings in order to devise the effective elements through which the Muslim personality based on firm foundations is built. The study concluded that the Muslim personality is based on true faith and charity in good deeds, which is the fruit of faith, and in it the goodness of the individual and society is, and the more the individual upholds his principles, values and faith, the more this contributes to the goodness of the whole society. And in Surah al-Kahf, there are stories that point to the practical methods that helped to create the Muslim personality of all the mentioned types. Just as faith is linked to knowledge, and knowledge is linked to strength and empowerment, so the sequence is clear in the stories mentioned in Surah al-Kahf, so the story of the Companions of the Cave is linked to faith, and that money helps with knowledge, and it is linked to the story of the Companions of the Two Gardens. And a flag that helps with strength and empowerment appears in the story of Moses and al-Khidr, and if the intentions are sincere, this is crowned, and this is evident in the story of Dhul-Qarnayn.